Unintentional doping through the use of contaminated nutritional supplements - van der Merwe, P J; Grobbelaar, E (South African medical journal, 2005)
To determine whether the intake of contaminated nutritional supplements could cause an athlete to fail a dope test. A contaminated nutritional supplement was used, identified in an ongoing study screening over-the-counter nutritional supplements. One capsule of the supplement, containing small amounts of 19-nor-4-androstenedione and 4-androsten-3,17-dione, not listed on the label, was administered to 5 healthy male volunteers. Fractional urine collection was done at prescribed intervals. Outcome measures. The samples were analysed using gas chromatography/mass spectrometry (GC/MS). Samples containing 19-norandrosterone, the main metabolite of 19-nor-4-androstenedione, were quantified using GC/MS. All the volunteers had urinary concentrations of 19-norandrosterone above the World Anti-Doping Agency threshold of 2 ng/ml from 2 hours post administration. In 2 volunteers 19-norandrosterone above the threshold value could still be detected beyond 36 hours post administration. The highest concentration of 19-norandrosterone found in a sample was 54.6 ng/ml at 8 hours post administration. The results of this study showed that the intake of microgram amounts of a prohibited substance in a nutritional supplement could cause an athlete to fail a dope test.